The effect of phosphorus on rumen and blood metabolites of angora goats - Mehmet Kocabatmaz; Mursayettin Eksen; Zafer Durgun (Eurasian Journal of Veterinary Sciences)
In this investigation, three Angora Goats of 3 years old and with the permanent rumen cannula were used. The goats were fed with alfalfa hay (40%) and the pelleted white beet pulp (60%). The first animal was used as a control and 1 g and 2.4 g phosphorus were infused via rumen cannula into rumen of the second and third animals respectively. Rumen content and blood samples were taken before feeding and at the 3rd and 6th hour after feeding with 7 days intervals. The pH values of rumen contents were highest before feeding and generally lowest at 6th hour after feeding for all animals. At the each sampling time, the average values of protozoa counts and percentage of Isotricha intestinaiis, Isotricha prostoma and Dasytricha ruminantium for second and third animals to which phosphorus (Ig and 2.4 g respectively) infused were highest than first animal but the percentage of Entodinium minimum and Entodinium caudatum showed decrements for second and third animals. On the other hand, the highest NH3 - N values of rumen contents were determined for the second animal at each sampwling time but same values were lowest for first animal. Before feeding, urea-N of blood was highest and showed gradually decrements after feeding for first animal. The same values were found to be lowest before feeding, and showed increments for second animal at other sampling times. All of the total protein values generally were equal for ail animals. The glucose values of blood sera beiongig to the third animal were found higher than the other animals only the lower values of glucose at the before feeding showed gradually incaremets after feeding for all animals. In addition before of the effect of phosphate infusion, inorganic phosphorus values of rumen contents and blood sera of the second and third animals were higher than the first animal at each sampling time.